Sodium-23 magnetic resonance imaging during and after transient cerebral ischemia: multinuclear stroke protocols for double-tuned 23 Na/ 1 H resonator systems - Wetterling, Friedrich; Ansar, Saema; Handwerker, Eva (Physics in medicine and biology, 2012)
A double-tuned 23 Na/ 1 H resonator system was developed to record multinuclear MR image data during and after transient cerebral ischemia. 1 H-diffusion-, 1 H perfusion, 1 H T 2 -, 1 H arterial blood flow- and 23 Na spin density-weighted images were then acquired at three time points in a rodent stroke model: (I) during 90 min artery occlusion, (II) directly after arterial reperfusion and (III) one day after arterial reperfusion. Normal 23 Na was detected in hypoperfused stroke tissue which exhibited a low 1 H apparent diffusion coefficient (ADC) and no changes in 1 H T 2 relaxation time during transient ischemia, while 23 Na increased and ADC values recovered to normal values directly after arterial reperfusion. For the first time, a similar imaging protocol was set-up on a clinical 3T MRI site in conjunction with a commercial double-tuned 1 H/ 23 Na birdcage resonator avoiding a time-consuming exchange of resonators or MRI systems. Multinuclear 23 Na/ 1 H MRI data sets were obtained from one stroke patient during both the acute and non-acute stroke phases with an aquisition time of 22 min. The lesion exhibiting low ADC was found to be larger compared to the lesion with high 23 Na at 9 h after symptom onset. It is hoped that the presented pilot data demonstrate that fast multinuclear 23 Na/ 1 H MRI preclinical and clinical protocols can enable a better understanding of how temporal and regional MRI parameter changes link to pathophysiological variations in ischemic stroke tissue.
Gesehen am 29.10.2018